2021
DOI: 10.3390/genealogy5040099
|View full text |Cite
|
Sign up to set email alerts
|

Marae Ora Kāinga Ora: Indigenous Health and Wellbeing Solutions via Time-Honored Indigenous Spaces

Abstract: Marae Ora, Kainga Ora (MOKO) is a three-year research study established as a marae-led intervention project to strengthen the provision of housing with five urban marae in South Auckland, Aotearoa New Zealand. In brief, marae are primarily places for cultural gatherings and are the centres of activity for Māori communities. Though just one of the marae involved is part of a pre-European tribal settlement, the four other marae were established to meet the cultural needs of Māori who had relocated many decades a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Another Australian study examining urban Aboriginal populations found that successful outcomes, such as employment, were linked with educational attainment and interaction with the justice system (Reeve & Bradford, 2014). Lee-Morgan et al (2021) proposed that wellbeing solutions for the M aori Indigenous people of New Zealand incorporate M aori culture and a more holistic perspective into policy. Chetty et al (2020) found that the Indigenous population in the United States had lower rates of upward mobility and higher rates of downward mobility than the Caucasian population, leading to intergenerational socioeconomic gaps.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Australian study examining urban Aboriginal populations found that successful outcomes, such as employment, were linked with educational attainment and interaction with the justice system (Reeve & Bradford, 2014). Lee-Morgan et al (2021) proposed that wellbeing solutions for the M aori Indigenous people of New Zealand incorporate M aori culture and a more holistic perspective into policy. Chetty et al (2020) found that the Indigenous population in the United States had lower rates of upward mobility and higher rates of downward mobility than the Caucasian population, leading to intergenerational socioeconomic gaps.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee‐Morgan et al . (2021) proposed that well‐being solutions for the Māori Indigenous people of New Zealand incorporate Māori culture and a more holistic perspective into policy.…”
Section: Literature Reviewmentioning
confidence: 99%

Feeding Indigenous Aotearoa better

Smith (Waitaha, Kāti Māmoe, Kāi Tahu),
Hutchings (Ngāti Huirapa and Gujarat, India)
2024
Journal of the Royal Society of New Zealand